A series of 10 Polish patients with thromboembolic events and antithrombin deficiency: two new c.1154-1 G>C and c.1219-534 A>G SERPINC1 gene splicing mutations. Issue 5 (July 2019) - Wójcik, Magdalena; de la Morena-Barrio, María E.; Michalik, Justyna; Wypasek, Ewa; Kopytek, Magdalena; Corral, Javier; Undas, Anetta
Abstract : N/A: Inherited antithrombin (AT) deficiency, with prevalence in the general population ranging 0.02–0.17%, is an autosomal dominant disorder associated with a high risk of venous thromboembolism. In most cases, deficiency is caused by mutations in the AT-coding gene ( SERPINC1 ). Only 24 splicing defects have been described causing AT deficiency, all affecting exon flanking regions. The aim of the current study was to characterize the mutations underlying AT deficiency in 10 venous thromboembolism Polish patients aged 42.9 (14–63) years. Whole SERPINC1 gene sequencing was done by next generation sequencing methods. Eight cases had mutations previously described. However, we identified two new intronic mutations that might affect the correct splicing of exon 6 according to in-silico predictions: c.1154-1 G>C, which strongly disturbs the acceptor sequence and c.1219-534 A>G, a deep intronic mutation that might generate a cryptic donor sequence; both might compete with the wild-type donor sequence and explain the associated moderate AT deficiency of carriers. In conclusion, we show the molecular base of AT deficiency in 10 new Polish patients, including two novel SERPINC1 gene mutations potentially affecting splicing.